The Streptococcus mutans ability to survive in biofilms and during dental caries formation: scoping review - Anisauma UTAMANİNGYAS; Hening Tjaturina PRAMESTİ; Felisha Febriane BALAFİF (Journal of Syiah Kuala Dentistry Society, 2022)
Caries are the deterioration of dental hard tissue caused by acidic byproducts of bacterialcarbohydrate fermentation. The formation begins within the bacterial biofilm that covers the tooth's surface. Streptococcus mutans is the dominant bacteria in the biofilm, forming a multispecies biofilm on the tooth surface, growing, and surviving within it. S. mutans colony formation and acid formation can lead to tooth demineralization. The purpose of this scoping review is to determine the ability of S. mutans to survive in biofilms and during the formation of dental caries using articles from the chosen database. Articles published from 2016 until 2021 were searched for using the keywords: "Streptococcus mutans and caries or dental caries and survival ability or survivability and survival factor" in the PubMed, ScienceDirect, Cochrane, and Google scholar databases. Using PRISMA-Scr, existing articles were chosen based on inclusion and exclusion criteria. There were ten articles found that were suitable for review. The data presented in the article vary according to the study's location, purpose, method, and samples. The finding revealed that S. mutans survive in biofilms and caries formation due to their ability to activate enzymes, virulence factors of S. mutans, and the environmental conditions of the oral cavity. Aciduric; acidogenic; quorum sensing; ability to form GTFs, GBPs, ATPase, CSP, eDNA; and the ability to produce bacteriocin and autolysins all contribute to Streptococcus mutans' ability to survive in biofilms and during the formation of dental caries KEYWORDS: biofilm, caries, survival ability, survival factor, Streptococcus mutans.